Profile of Patients with Placental Abruption in Ultrasonography - Miyamura Namiuchi, Nickolas Yugo; Fortaleza de Melo, João Italo; Dutra, Luiz Dias; Ramos Franco Netto, Raphael Oliveira; Ramos Fernandes, Victor Augusto; Manfredini, Rebecca Corrêa; Mendonça, Messias Villa; Rocha, Fabio; Rodrigues Franco Netto, Juliana de Almeida; Delgado do Amaral, Kayque Wellek; Baggio Namiuchi, Gabriela Kamiji (International Journal of Innovative Research in Medical Science, 2020)
Objective: The objective of this study was to evaluate the incidence of placental abruption (PA) among nulliparous and multiparous women in the city of Dourados-MS Brazil. Materials and methods: Retrospective single-center cross-sectional study. 240 examinations of patients submitted to ultrasonography (USG) with medical indications for investigating PA were evaluated. Results: The average age was 28.6 ± 6.38, minimum 15 and maximum 43 years. The patients’ weeks of pregnancy showed an average of 7.8 ± 3.1 minimum 4 and maximum 27 weeks. PA occurred in 66 (27.7%) of the patients out of the 240 evaluated patients. Conclusion: The occurrence of PA in the studied population was high. There was no correlation between the occurrence of PA and the age of the patients. The relevance of family planning and adequate prenatal care in the early identification of risk factors for PA, as both contribute to reducing the incidence of unfavorable pregnancy outcomes.